Computation of Optical Properties of Core-Shell Super-Spheroids Using a GPU Implementation of the Invariant Imbedding T-Matrix Method - Bi, Lei; Wang, Zheng; Han, Wei; Li, Weijun; Zhang, Xiaoye (Frontiers in Remote Sensing, 2022)
Particles with internal inclusions or cores are ubiquitous in the atmosphere. One example is dust particles coated with water-soluble aerosols such as sulfate or nitrate. For these particles, the dust non-sphericity and the core-shell structure of the particle both fundamentally impact the optical properties. However, it is challenging to obtain an accurate and comprehensive parameterization of the optical properties of coated atmospheric particles. Recent studies have found that super-spheroids could provide a robust model for representing the non-sphericity of irregular particles, such as dust, sea salt, and ice particles. This important finding warrants further investigations on coated super-spheroids for the development of mixed-aerosol models. In this study, we developed a GPU version of the invariant imbedding T-matrix program (GPU-IITM) to improve the computational efficiency. This version allows for efficient computation of the optical properties of coated super-spheroids with extensive shape parameters and refractive indices. The GPU-IITM is 8–25 times more efficient than the conventional CPU-IITM, depending on the size parameter of the coated super-spheroids. The single-scattering properties of coated super-spheroids computed from the GPU-IITM allows for close examination of the optical differences between homogeneous and inhomogeneous particles. As an example, we present the linear depolarization ratios (LDRs) of coated super-spheroids, which have implications in active lidar remote-sensing research. We found that the LDR decreases obviously as the real part of the shell’s refractive index increases from 1.3 to 1.6. Greater LDRs occur for particles with a thin coating, while a rounder shape of the particle decreases the LDRs. However, special attention should be given to nearly spherical particles, for which the LDRs could be enhanced. In comparison to homogeneous particles, the degree of enhancement decreases or increases depending on whether the shell’s refractive index is smaller or larger than the core refractive index.